Cytometric blood phenotyping in free-living white-eyed parakeet (Psittacara leucophthalmus) - Cruz, Nathan R.n. [UNESP]; Santi, Mariele De [UNESP]; Braz, Larissa Ayane N. [UNESP]; Werther, Karin [UNESP]; Santana, Áureo E. [UNESP] (Colégio Brasileiro de Patologia Animal - CBPA, 2021)
This study aimed at performing cytometric phenotyping of the blood samples from free-living, young white-eyed parakeets (Psittacara leucophthalmus), stained with 3,3-dihexyloxacarbocyanine [DiOC6(3)]. DiOC6(3)-stained whole blood samples from 19 free-living, young white-eyed parakeets were analyzed by flow cytometry and cell types were distinguished by their typical fluorescence in blue laser channel (FL-1) and SSC (side scatter). It was possible to differentiate erythrocytes (58.3±13.6) from leukocytes (32.4±13.1) and some of the leucocyte subpopulations: lymphocytes/thrombocytes (29.7±7.7), monocytes (30.6±8.5), and granulocytes (5.9-26). However, lymphocytes and thrombocytes could not be sorted in the plots. Our study determined that the predominant population in white-eyed parakeet (P. leucophthalmus) was lymphocytes, thrombocytes, and monocytes in the leucocytes gates in comparison to the granulocyte population. The cytometry method and use of DiOC6(3) stain was available for parakeets blood samples and can be studied and applied to other species of parrots.

Este estudo teve como objetivo realizar a fenotipagem citométrica com 3,3-di-hexiloxacarbocianina [DiOC6 (3)] de amostras de sangue de maritacas jovens de vida-livre (Psittacara leucophthalmus). As amostras de sangue total, coradas com DiOC6(3) de 19 maritacas de vida livre, foram analisadas por citometria de fluxo e os tipos de células foram distinguidos por sua fluorescência típica no canal laser azul (FL-1) e SSC (dispersão lateral). Foi possível diferenciar eritrócitos (58,3±13,6) de leucócitos (32,4±13,1) e algumas subpopulações de leucócitos: linfócitos/trombócitos (29,7±7,7), monócitos (30,6±8,5) e granulócitos (5,9-26), entretanto, linfócitos e trombócitos não puderam ser diferenciados em duas populações distintas. Nosso estudo determinou que a população predominante P. leucophthalmus foi mononuclear agranulocítica em comparação com a taxa de aquisição da população granulocítica. A metodologia de citometria de fluxo com uso da coloração de DiOC6(3) foi aplicável a amostras sanguíneas das maritacas e pode ser estudado e aplicado para outras espécies de psitacídeos.
Fenotipagem citométrica do sangue de maritacas jovens de vida-livre (Psittacara leucophthalmus)
Keywords: White-eyed parakeet; Psittacara leucophthalmus; Psittaciformes; avian; flow cytometry; blood cell phenotyping; leukocytes; DiOC6(3); wildlife animals; Maritacas; Psittacara leucophthalmus; Psittaciformes; aves; citometria de fluxo; fenotipagem; leucócitos; DiOC6(3); animais selvagens